The Influence of Digital Platforms, Content Quality and Target Market on Political Campaigns - Amaroso, Russell; Mei Liana, Hany (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
The effect of Digital Platform, Kualitas konten and Target Market on Kampanye Politik is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Digital Platform has an effect on Kampanye Politik; 2) Kualitas konten has an effect on Kampanye Politik; and 3) Target Market has an effect on Kampanye Politik.